Amphibians and Irrawaddy Dolphins Conservation Awareness Programmes - Das, Indraneil; Cindy, Peter (UMINAS Publisher, 2020)
Two conservation awareness programmes funded under the Shell Chair are the International Frog Race, and Sarawak Dolphin Project Community Outreach and Education (SDPCOE). The programmes are organized by IBEC with supports (in kind or finance) from other agencies such as Sarawak Forestry Corporation, Ministry of Tousirm and Culture Malaysia, Sarawak Tourism Board, local banks, tourism operators, NGOs and local communities.